Pengembangan Media Monopoli Digital Berbasis Flippity Untuk Meningkatkan Hasil Belajar Kognitif Keberagaman Budaya Indonesia Kelas V B SDN Wonosari 01 - Dewi, Syahrani Wahyu; Widodo, Susilo Tri (Universitas Muhammadiyah Magelang, 2025)
This research aims to develop a Flippity-based digital monopoly learning media to improve the learning outcomes of Indonesian cultural diversity in grade V B SDN Wonosari 01 Semarang students. This research uses the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subject in this study is a student of grade V B SDN Wonosari 01. The data collection techniques used include interviews, media feasibility validation questionnaires by media and material experts, and user response questionnaires to measure the practicality and effectiveness of media. The results of the media feasibility test showed an average score of 78% for media feasibility and 87.5% for material eligibility, with an overall average of 82.7%, which falls into the very feasible category. Practicality analysis showed that this medium was very practical with an average score of 94% for teacher responses and 97.2% for student responses. The effectiveness test using a paired t-test yielded a significance value of 0.000 < 0.05 and an average N-Gain value of 0.77, indicating a significant improvement in learning outcomes in the high category. Based on the results of the study, the Flippity-based digital monopoly learning media was stated to be very valid, very practical, and effective in improving the learning outcomes of Indonesian cultural diversity in grade V students of SDN Wonosari 01.